Project-Based Learning in Science Education: A Meta-Analysis Study - Nurhasnah, Nurhasnah; Festiyed, Festiyed; Asrizal, Asrizal; Desnita, Desnita (FKIP Universitas Lampung, 2022)
Project-based learning model is one model that is widely used in science learning. Based on this, the relevant literature was reviewed for the Identification of the Effects of Science-Based Learning Project (physics, chemistry, biology, and science) at all levels of education, starting from elementary, junior high, high school, and university levels. Procedures performed; (1) searching and collecting national and international articles through google scholar (2) determining articles according to the characteristics and research criteria, (3) classifying and categorizing articles according to research variables (4) analyzing the pretest and post-test data of articles. This study examines the findings of 25 articles conducted through a meta-analysis to be able to provide conclusions on the effect of project-based learning models in science learning. The magnitude of the influence of PBL in science learning is 1.67 with a high category according to Cohen. This means that the project-based learning model is effectively applied in science learning. Keywords: project-based learning, meta-analysis, science education.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp198-206